Interaktionstechniken für mobile Augmented-Reality-Anwendungen basierend auf Blick- und Handbewegungen - Hammer, Jan Hendrik (Karlsruher Schriften zur Anthropomatik, 2022)
Intuitive interaction techniques are essential for mobile augmented reality systems. For implicit interaction, this work presents techniques for automatic eye movement analysis and visualization. In the context of explicit interaction, a fusion of optical flow, skin color segmentation, and a hand pose estimator is presented along with a tracking method for localization and pose estimation of a hand in monocular color images.